Cyclic behaviours of soft silty clay with long-term traffic loading considering drainage conditions - Jiang, Yexiang; Li, Ruofei; Su, Fengyang; Chen, Guanyu; Xia, Chaobo; Tong, Junhao; Wu, Tingyu (Frontiers in Built Environment, 2024)
The traffic loading is a typical cyclic loading with variable confining pressure and always lasts long, and is believed to have a significant effect on the subgrade soil, especially for the subgrade filled with soft clay. However, the mechanics have yet to be fully understood. Given that the duration of traffic loading lasts long enough, the partially drained conditions should be considered for the soft clay under the long-term cyclic loading, rather than the undrained conditions adopted commonly by most previous researches. In this study, 28 cyclic tests were conducted on the remolded saturated soft clay, utilizing both constant confining pressure and variable confining pressure under partially drained and undrained conditions. The effect of cyclic confining pressure and different drainage conditions is analyzed in relation to the evolution of pore pressure and deformation behaviors. Incorporating both the cyclic confining pressure and cyclic stress ratio, a concise pre-diction model of permanent strain is proposed and validated by the experimental results.